Acute Care Surgery during the COVID-19 pandemic in Spain: Changes in volume, causes and complications. A multicentre retrospective cohort study. (August 2020) - Cano-Valderrama, Oscar; Morales, Xavier; Ferrigni, Carlos J.; Martín-Antona, Esteban; Turrado, Victor; García, Alejandro; Cuñarro-López, Yolanda; Zarain-Obrador, Leire; Duran-Poveda, Manuel; Balibrea, José M.; Torres, Antonio J.
Abstract: Background: during the COVID-19 pandemic, the number of Acute Care Surgery procedures performed in Spanish hospitals decreased significantly. The aim of this study was to compare Acute Care Surgery activity during the COVID-19 pandemic and during a control period. Material and methods: a multicenter retrospective cohort study was performed including patients who underwent Acute Care Surgery in three tertiary care hospitals in Spain during a control (11 th March 2019 to 21 st April 2019) and a pandemic (16 th March 2020 to 26 th April 2020) period. Type of surgical procedures, patients' features and postoperative complications were compared. Results: two hundred and eighty-five and 117 patients were included in each group. Mean number of patients who underwent Acute Care Surgery during the control and pandemic periods was 2.3 and 0.9 patients per day and hospital (p < 0.001), representing a 58.9% decrease in Acute Care Surgery activity. Time from symptoms onset to patient arrival at the Emergency Department was longer during the pandemic (44.6 vs. 71.0 h, p < 0.001). Surgeries due to acute cholecystitis and complications from previous elective procedures decreased (26.7% vs. 9.4%) during the pandemic, while bowel obstructions and abdominal wall hernia surgeries increased (12.3% vs. 22.2%) (p = 0.001). Morbidity was higher during pandemic period (34.7% vs. 47.1%, p = 0.022), although this difference was not statistically significant in the multivariate analysis. Reoperation rate (17.9% vs. 12.8%, p = 0.212) and mortality (6.7% vs. 4.3%, p = 0.358) were similar in both groups. Conclusion: during the COVID-19 pandemic, a significant reduction in the performance of Acute Care Surgery procedures was observed. Moreso, a longer time from symptoms onset to patient arrival at the Emergency Department was noted. Higher morbidity was observed in patients undergoing Acute Care Surgery during the pandemic period, although there was not any difference in mortality or reoperation rate. Highlights: Acute Care Surgery Activity was decreased during the COVID-19 pandemic. A higher delay of the patients presenting in the Emergency Department was observed during the pandemic period. During the COVID-19 pandemic, a higher morbidity rate was found in patients undergoing Acute Care Surgery.